EDUKASI AIR SUSU IBU EKSLUSIF PADA IBU MENYUSUI DI KELURAHAN BATUANG TABA NAN XX KECAMATAN LUBUK BEGALUNG KOTA PADANG - Desmawati Desmawati; Miranie Safaringga; Marzatia Yulika; Auwilla Marta Tasman; Novi Aulia Driza; Siti Aisyah; Asti Marian Sari; Kiran Nandini Fijri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Exclusive breastfeeding is the best life liquid that is needed by babies which contains various substances that are important for the growth and development of babies and according to their needs, Exclusive breastfeeding is giving only breast milk to babies up to 6 months of age without additional fluids or other foods. Based on secondary data obtained from the implementation of community field work practices, conducted in RW 01 Batuang Taba Village, November 14-18 2022 there were 63% of mothers who breastfed did not give exclusive breastfeeding. So the authors try to intervene with health education methods to mothers of babies about exclusive breastfeeding in the local area. The method used in this activity is an analytical survey. It is hoped that using this method can help increase knowledge about exclusive breastfeeding. Based on the analysis of the pretest and posttest questionnaires given to 6 respondents, it can be seen the distribution of the answers obtained before and after the intervention. Knowledge percentage increased significantly. At the time of the pretest, 83.3% of mothers had less knowledge and 16.7% had sufficient knowledge. After the intervention and posttest were carried out, it was found that 50% of mothers had good knowledge, 33.3% had sufficient knowledge, and 16.7% had poor knowledge. . The results of this activity showed that the mother's knowledge increased significantly. At the time of the pretest, 83.3% of mothers had less knowledge and 16.7% had sufficient knowledge. After the intervention and posttest was carried out, it was found that 50% of mothers had good knowledge, 33.3% had sufficient knowledge, and 16.7% had poor knowledge.